Influence Distribution Logistics to Smoothness Operational Ships at PT. Humpuss Transportasi Kimia - Larsen Barasa; April Gunawan Malau; Damayanto Purba; Dika Handika Munajat (Dinasti Publisher, 2022)
Humpuss Transportasi Kimia is a company private sector engaged in shipping. Based on the data, the existing problems discuss the distribution of logistics for the smooth operation of the ship. The purpose of this study is to determine and analyze the extent to which the influence of distribution logistics to smooth operational ships at PT. Humpuss Transportasi Kimia. The research was conducted by processing data from the distribution status distribution goods logistics on ships and operational performance boat PT. Humpuss Transportasi Kimia. Type research used is method quantitative. Data collection is carried out with distributed questionnaire direct to 20 related respondents with procurement and delivery goods operational ships, namely the division of procurement, logistics, and operations. In looking for results calculated using the SPSS 24.0 program and some data analysis, namely: analysis statistics descriptive, instrument test, assumption test classic, coefficient test correlation, coefficient test determination, and hypothesis testing. Withdrawal conclusion in the study this conducted by comparing the data obtained from answer respondents. based on the acquisition of questionnaire data and data processing. Retrieved amazing results that variable distribution logistics take to effect positive by significant to smoothness operational boat with t count > t table or 3,739 > 2,100